The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/f8100365
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Changes in Water Use Efficiency to Understand Drought Induced Tree Mortality

Abstract: Forests are becoming increasingly vulnerable to rising tree mortality rates in response to warming and drought. In California, the most severe drought on record occurred from 2012 to 2016 and high tree mortality rates were observed in response to this prolonged drought. Differences in satellite-derived estimates of water-use efficiency (WUE) under normal (i.e., WUE BASELINE ) and drought conditions (∆WUE = WUE 2014 − WUE BASELINE ) captured variation in drought resilience, and is used here to understand patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…They have strong effects on the local climate (Li et al, 2015), by interacting with biogeochemical water cycles (Ellison et al, 2017). When forest trees die or forests are cleared across large-scale landscapes, the negative consequences of drought are aggravated (Allen et al, 2015; Reyer et al, 2015), as shown for many areas world-wide (Laurance, 1998, 2004; van der Werf et al, 2008; Malone, 2017). Over-utilization of forests as a feedstock for energy, construction materials, or the generation of value-added products for the chemical industries, intensifies the problem.…”
Section: Introductionmentioning
confidence: 99%
“…They have strong effects on the local climate (Li et al, 2015), by interacting with biogeochemical water cycles (Ellison et al, 2017). When forest trees die or forests are cleared across large-scale landscapes, the negative consequences of drought are aggravated (Allen et al, 2015; Reyer et al, 2015), as shown for many areas world-wide (Laurance, 1998, 2004; van der Werf et al, 2008; Malone, 2017). Over-utilization of forests as a feedstock for energy, construction materials, or the generation of value-added products for the chemical industries, intensifies the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Monthly scPDSI data made available through the Western Regional Climate Center ranges from −6.0 to 6.0. The number shows the magnitude and the sign denotes (+) wetter than average or (−) drier than average conditions for a location based on historical climate and sensitivity to changes in water availability [ 43 , 44 , 45 ]. Values of scPDSI between −0.4 and 0.4 denote average conditions, and absolute values greater than 4 represent extreme conditions.…”
Section: Methodsmentioning
confidence: 99%
“…ac. uk/ cru/ data/ droug ht/) (Malone 2017;Osborn et al 2016;Osborn et al 2017). In this study, annual of scPDSI was calculated by monthly means of scPDSI.…”
Section: Gpp Et and Scpdsi Datamentioning
confidence: 99%